The phenomenon of the Islamic Spiritual Youth Da'wah Movement of Pekanbaru City - Hartono, Toni (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2019)
This article examines the phenomenon of the Islamic spiritual youth da'wah movement in Pekanbaru. Da'wah movement in this context to deepen and strengthen Islamic teachings. The spiritual function of Islam is a forum, teaching, preaching, and sharing Islamic knowledge. This study uses qualitative methods to understand the phenomena of their da'wah movements. The data obtained were analyzed by the phenomenology approach. The study results show that Islamic spiritual youth make the organization a forum for their activities and exercises. The finding indicates that Islamic spiritual organization uses a platform for change movements, Islamic coaching, syiar and da'wah, Islamic activities, strengthening friendship, and social solidarity. Artikel ini mengkaji fenomena gerakan dakwah remaja Rohani Islam Kota Pekanbaru. Gerakan dakwah dalam konteks ini untuk memperdalam dan memperkuat ajaran Islam. Fungsi Rohani Islam adalah sebagai forum, pengajaran, dakwah, dan berbagi pengetahuan Islam. Kajian ini menggunakan metode kualitatif untuk memahami fenomena gerakan dakwah mereka. Data yang diperoleh dianalisis dengan pendekatan fenomenologi. Hasil kajian menunjukkan bahwa remaja Rohani Islam menjadikan organisasi sebagai wadah untuk kegiatan dan gerakan dakwah mereka. Fakta ini ditunjukkan dengan temuan bahwa organisasi Rohani Islam dijadikan sebagai wadah gerakan perubahan, wadah pembinaan keislaman, wadah syiar dan dakwah, wadah kegiatan Islam, wadah mempererat silaturrahmi, dan wadah solidaritas sosial.